GUERRA E PAZ EM HISTORIAE ADVERSUS PAGANOS: PAULO ORÓSIO E A REPRESENTAÇÃO DE UMA NOVA ORDEM IMPERIAL SOB A ÉGIDE CRISTÃ (SÉCULO V D.C.) - Oliveira, Gabriella Torres de (2021)
This dissertation analyses the work “Historiae adversus paganos”, written by Bracarense presbyter, Paul Orosius, during the fifth century A.D. We seek with this analysis better comprehend the representation of the historical events, in a bias of conflicts between pagans and Christians, in the Late Antiquity. We believe that, the establishment of dichotomous pairs, like war and peace, pagan and Christian eras, are a rhetorical strategy of the author in a sense to propose a Christian narrative in a context of political instability inside the Roman Empire in the fifth century A.D. The context of the period marked the narratives of the epoch, Christians and pagans searched for answers, be it blaming one another, interpretation of religious character or analysis politico-military. Orosius is precisely inserted between those who formulated answers for the epoch. The author of “Historiae” utilizes the historical events to legitimize his apologetic discourse, refuting the countless accusations of pagans against Christians, but mainly as a method to corroborate his thesis: that the events inside the Roman Empire were the firstfruits of the building of a new imperial order based on the concord of Christiana Tempora. In describing the history of humanity, from Adam until the beginning of the fifth century, his objective was precisely demonstrating the superiority of the Christian period, in comparison to the pagan period. Consequentially, the author organizes his historical analysis, which apex for the Christians is during the rule of August Emperor, with the birth of Jesus Christ. From that moment, the justifications for the misfortunes began, in a way that the biggest woe would be considered small, in sight of what was to come, the advent of a new Christian Imperial Order.